The impact of banking diversification and capital adequacy indicators in market Value: Analytical study in a sample of banks registered in the Iraqi Stock Exchange for the period (2005-2019) - Sudad Ali Abd AlAbbass; Ali Ahmed Faris; Ahmed Khadum Braies (Iraqi Journal for Administrative Sciences, 2024)
The aim of study is test the relationship between banking diversification and capital adequacy indicators in market value. A sample of Iraqi private commercial banks was selected for the period (2005-2019) based on financial reports published in the Iraqi Stock Exchange. in order to measure the variables of the study, the researcher depend on financial (diversification and capital adequacy) and Suitable statistical equations for it . The relationship between the variables of the study, the researcher Tested the variables and found the relationships between the variables of the study and a result that contributes to the impact of independent variables in the dependent variables according to statistical tests used for this purpose and based on the statistical program (SPSS V.23) and the economic measurement program (Eviews 10) and the use of Panel Data based on pooled OLS and Fixed effects least square dummy variable (LSDV). Banking and capital adequacy indicators in the market value of the banks sample study and within the chosen time period).